The Relationship Between Mother's Knowledge About Nutritious Food and the Incidence of Stunting in Toddlers in Gunungagung Village - Amirul Mukminin; Ilda, Wildatuna Durotunisa (BELIA Early Childhood Education Papers, 2025)
One of the problems regarding nutrition in Indonesia, especially the problem that occurs in Gunungagung Village, is stunting. Stunting is a disease that is declared chronic and has an impact on the development and growth of stunted sufferers. One of the contributing factors is a lack of nutritional intake. The behavior of providing nutritional intake to toddlers is influenced by a mother's knowledge. Therefore, a mother's knowledge of preparing a nutritious food menu can ensure good nutrition. The aim of this research is to find out and identify the characteristics of respondents from mothers based on age, education, occupation and characteristics of respondents from toddlers based on age and gender, mothers' knowledge about nutritious food, categories of stunting incidents that occur in toddlers and the relationship between mothers' knowledge about food. nutrition and the incidence of stunting among toddlers in Gunungagung Village. This research uses quantitative with a cross sectional design. Sampling used total sampling technique. With a total sample of 48 respondents, the data collection was observation, questionnaires, interviews and documentation. Data analysis used univariate and bivariate analysis (chi square) and correlation. The results of this research are that a p-value of 0.000 is <0.05, so H0 is rejected and H1 is accepted and the correlation is weak in the form of a negative correlation. Based on the results of this description, it can be decided that there is a relationship between maternal knowledge about nutritious food and the incidence of stunting among toddlers in Gunungagung Village with a correlation value of -292 with a weak correlation level.